Analysis of adaptive video streaming for users with demand heterogeneity - Issa, Sinzobakwira; Khalifa, Othman Omran; Gunawan, Teddy Surya (2018)
The revolution of smart phones and other electronic gadgets have increased the attention given to video streaming phenomena. The demand of video quality has also augmented as the number of users keeps on growing. This has toughened the distribution of bandwidth. It is becoming more challenging for service providers to cope with varied demand of video quality. In real life, users change frequently their demand of video quality. To mitigate these problems, an adaptive streaming approach was proposed to solve the problem related to users’ heterogeneous demands. A linear programing approach based on demand and supply was used to analyse and sustain user with low bandwidth. Enhancement Fractional Participative Scheme (EFPS) based on bandwidth contribution was explored. Using JSVM9.14 software, the simulated result shows that the optimized algorithms and enhancement structure improve the performance.